Irving Berlin's Easter parade [videorecording (DVD)] - Walters, Charles, 1911-1982; Garland, Judy; Astaire, Fred; Lawford, Peter, 1923-1984; Miller, Ann, 1923-2004; Stradling, Harry, 1901-1970; Berlin, Irving, 1888-1989; Altman, Robert, 1925-2006 (Warner Home Video, 2005)
Astaire is trying to forget ex-dance partner Miller while rising to stardom with Garland. Too good to watch just at Easter time.